Efektivitas Program Pengentasan Kemiskinan: Studi di Nagari Sungai Pinang - Retno Anggraini; Indraddin Indraddin; Azwar Azwar (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
Poverty is a very complicated problem to solve, even though there have been many poverty alleviation programs that have been intensified by the goverment. Both form the Soeharto era to the current era of Joko Widodo administration. The program is either empowerment or charity. However , property alleviation programs cannot reduce poverty rates, one of which is in Nagari Sungai Pinang where the poverty rate has increased. This study aims to identify the effectiveness of poverty alleviation programs in Nagari Sungai Pinang. This research analysis tool uses the theory of community empowerment according to Jim Ife. The research methodology use a qualitative approach and observation methods, in-depth interviews, documentation studies ang Focus Group Discussions(FGD). This study shows that the poverty alleviation program in Nagari Sungai Pinang cannot be said to be effective. Either the program is empowering or Charity. This is because there is no proper management and group responbility for each of these aids.